Proton Exchange Membrane Fuel Cell Emulator Using PI Controlled Buck Converter - Himadry Shekhar Das; Chee Wei Tan; AHM Yatim; Nik Din bin Muhamad (Institute of Advanced Engineering and Science, 2017)
Alternative energy technologies are being popular for power generation applications nowadays. Among others, Fuel cell (FC) technology is quite popular. However, the FC unit is costly and vulnerable to any disturbances in input parameters. Thus, to perform research and experimentation, Fuel cell emulators (FCE) can be useful. FCEs can replicate actual FC behavior in different operating conditions. Thus, by using it the application area can be determined. In this study, a FCE system is modelled using MATLAB/Simulink®. The FCE system consists of a buck DC-DC converter and a proportional integral (PI) based controller incorporating an electrochemical model of proton exchange membrane fuel cell (PEMFC). The PEMFC model is used to generate reference voltage of the controller which takes the load current as a requirement. The characteristics are compared with Ballard Mark V 5kW PEMFC stack specifications obtained from the datasheet. The results show that the FCE system is a suitable replacement of real PEMFC stack and can be used for research and development purpose.